Morfologia da espermateca e forquilha genital de algumas espécies das subfamílias neotropicais de stratiomyidae (Insecta, diptera) - Godoi, Fabio Siqueira Pitaluga de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2006)
The female genital structures represented by spermatheca and genital fork contain valuable characters that make possible distinguish species and in many cases allow defining the systematic position of certain groups with more security and precision in association with the external morphological characters (Theodor, 1976). In this context a morphologic study of the female genitalia of the Stratiomyidae was made seeking the possible utilization of the spermatheca and genital fork like a source of new taxonomic characters to help the identification of female and the futures phylogenetic analyses of the group. In this study the spermatheca and genital fork of 35 species were examined belonging to 11 of the 12 subfamilies of Stratiomyidae: Parhadrestiinae, Chiromyzinae, Beridinae, Pachygastrinae, Clitellariinae, Hermetiinae, Chrysochlorininae, Sarginae, Raphiocerinae, Stratiomyinae e Nemotelinae. The exception is Antissinae without specimens studied due to its shortage in collections. Nor all of the species had its spermatheca studied because of the great difficult to obtain this structure through the dissection. For the preparation of the material it was necessary of the entire abdomen which was macerated at hot lactic acid 85% for variable time, depending of the sclerotized presented by the abdomen. After the maceration, the pieces were transferred for dug slides with glycerin, where the genitalia was dissected and their structures illustrated e characterized. As much the espermateca as genital fork they exhibited a series of characters of great systematic value, allowing it use in routine identifications associated to the external morphological characters and in studies of compared morphology. Contributing in this way for elucidate the likeness relationships among the taxa, supplying important characters for reconstruction of phylogenetic hypotheses.
Keywords: Diptera; Brachycera; Moscas